The Early Identity Exploration Scale—a measure of initial exploration in breadth during early adolescence - Kłym, Maria; Cieciuch, Jan (Frontiers in Psychology, 2015)
The existing models and measurement instruments concerning identity appear to primarily focus on adolescence and early adulthood, and studies extending identity research to younger stages of life are scarce. There has been a particular lack of instruments measuring the early stages of identity formation, especially the process of exploration, which has been portrayed as a central process during this particular period of life. Our aim is to help fill the gap in the literature and facilitate further studies of the exploration process by providing an appropriate instrument to measure exploration in breadth during early adolescence. As a coherent and mature sense of identity is closely associated with psychosocial well-being, an effective identity exploration scale will enable researchers to assess the predictors of young adolescents' well-being. We propose a model of identity exploration domains based on the literature and considering twelve exploration domains: physical appearance, free time, family, work, boyfriend-girlfriend relationships, own opinion formation, perception of own place in the life cycle, self-reflection, future, future family, outlook on life, and attitude toward rules. The study was conducted on a group of N = 454 adolescents (50% males, Mage = 13.04, SD = 0.98). Both reliability and structural validity, as verified by confirmatory factor analysis were satisfactory. The instrument is invariant across gender groups at the scalar level of measurement invariance.